Means of Arguments in Bank's Annual Reports (Journal of the College of Education for Women, 2019)
In line with the most recent trends in genre analysis (Swales, 1990; Bahatia,1993) and discourse studies on business communication (Dudley-Evans and St.John, 1998;Bargiela-Chiappini, F. and C. Nickerson, 1999, the article focuses on aparticular financial genre, Bank's Annual Reports (ARs). More in detail, in contrastin widespread claim about the purely financial and informative nature of ARs,addressing experts only, this paper aims at illustrating in accordance with Bexleyand Hynes (2003), and Burrough's (1986) considerations, that those reportsendeavour to promote the company image and to leave a positive impression onreaders. Generally speaking, companies communicate because they exist: they havea name, headquarters, offices, a logotype, and provide cosumers with products andservices that help people to come closer to the company's reality (Brioschi,1990:51). However, another type of communication exists, this of argumentation: itis essential to inform the public about the company's activity, to charge its mind(Cantoni, Di Blas, 2002) and to it act in a certain way. Thus, argumentation aims atconvincing the counterpart that a thesis should (not) be accepted by usingreasonable arguments that impress the hearer/ reader. More specifically,argumentation can be found in an extremely important economic and financial text:the ARs. These are considered comprehensible not only to experts but also thelayman: they develop arguments that are within everyone's reach; they use plainlanguage and effective stylistic devices in order to be readable, to delight andconvince the public (Mignini, 2005:1).(Some research so far has been based on the definition as well as the contentanalysis of ARs, and on their writing's techniques and strategies, but few had takeninto account their argumentative stylistic features and discursive (in the sense ofother-than-purely-financial) sections.There has been not much research focusing on argumentation in the economicand financial world up-to-now; in this paper the researcher examines howargumentation is carried on in banks ARs, what the most exploited topics are, andhow they are arranged to win the public over. A glance at the textual structure isgiven first so as to have an idea about how the readers are introduced into the bank'sworld. Then, an analysis of the most common topics and the way they are usuallypresented (their argument) is provided: examples are also given in order to clarifythe content. The corpus of material gathered for the analysis includes four Bank's ARs. Allthe selected ARs are published on the web between 2003 and 2006 by the followingprestigious big banks: Deutsche bank (2003), Bank of England Annual Report(2004), Raiffeisen Centrobank (2005), and Bank of America (2006).